Análisis hidro-sedimentológico 2d del comportamiento de un campo de espigones para la protección de márgenes en un río meandriforme. Issue 2 (2nd July 2020) - Farias, Hector Daniel; Domínguez Ruben, Lucas; Prieto Villarroya, y Jorge
ABSTRACT: Alluvial rivers show a highly dynamic morphological patterns, which cause problems in the operation and maintenance of infrastructure located in their environment. In these cases, it is necessary to design structures to control bank morphodynamic processes. This article describes the hydro-sedimentology of the meandering channel called río del Valle (Argentina), for which bank protection was implemented on its outer bank. This study zone was selected for the cutting of an embankment located on the outer bank of the channel due to the excessive lateral migration of the meander. Flow structure and bed morphology patterns are analyzed and discussed using the results of the application of the TELEMAC 2D model coupled to the Sisyphe morphological module. These results allow us to identify vector patterns of velocity and streamlines in the groyne field, showing the development of a recirculation flow between groynes, as well as the influence in the displacement of the core of maximum velocity towards the center of the channel along the bend apex. The bed evolution shows the vertical regrowth of the bed in the groyne field and the reduction of the point bar in the bend entrance.